Upaya Meningkatkan Kepuasan Konsumen Melalui Harga, Lokasi dan Fasilitas pada Classic Futsal Kediri - Heri Prasetio (Jurnal Simki Economic, 2019)
The background in this research is the rapid development of the sports facility rental business which makes business competition increase, so that the right marketing strategy is needed. In order for the company to achieve the expected target, the company must pay attention to the factors that affect customer satisfaction. The purpose of this study is to determine (1) the effect of price, location and facilities partially on consumer satisfaction Classic Futsal Kediri? (2) the effect of price, location and facilities variables simultaneously on consumer satisfaction. This research is a quantitative research with explanatory research techniques. The independent variables of this study are price (X1), location (X2), and facilities (X3), with the dependent variable is customer satisfaction (Y). The population of this research is all consumers or tenants in the Kediri Classic Futsal field. The sample used in this study were 70 respondents. The sampling technique used is simple random sampling with probability sampling method. The instrument in this research is a questionnaire (questionnaire). The analysis technique used is multiple linear regression analysis and hypothesis testing using SPSS software for windows version 21. The conclusions of this study are (1) price has a positive and significant effect on customer satisfaction, (2) location has a positive and significant effect on customer satisfaction, ( 3) facilities have a positive and significant effect on consumer satisfaction, (4) price, location, and facilities, together (simultaneously) have a significant effect on customer satisfaction.